2009
DOI: 10.1302/0301-620x.91b8.21882
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis of the brachial artery after closed dislocation of the elbow

Abstract: The brachial artery is rarely injured after closed dislocation of the elbow. We describe an unusual variation of this injury, namely, a delayed thrombosis of the brachial artery after a closed dislocation sustained during a low-energy fall. This has not previously been described in the English literature, but may be more common than this suggests. We stress the importance of a thorough neurovascular examination and vigilance in regard to this potentially disastrous complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…To our best knowledge, there are about 50 cases of brachial artery injuries after an elbow dislocation (closed, open, or with accompanying bone fractures) documented in the medi-cal literature (2,6). Fortunately, in the most cases, an arterial injury is present at the time of dislocation, but presentation can be delayed from the time when the patient is discharged from the hospital to ten days after closed reduction (5). It is shown that there are two patterns of the injury -a complete transection or an intimal tear followed by secondary thrombosis or formation of pseudo-aneurysm (2,6,8,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our best knowledge, there are about 50 cases of brachial artery injuries after an elbow dislocation (closed, open, or with accompanying bone fractures) documented in the medi-cal literature (2,6). Fortunately, in the most cases, an arterial injury is present at the time of dislocation, but presentation can be delayed from the time when the patient is discharged from the hospital to ten days after closed reduction (5). It is shown that there are two patterns of the injury -a complete transection or an intimal tear followed by secondary thrombosis or formation of pseudo-aneurysm (2,6,8,13).…”
Section: Discussionmentioning
confidence: 99%
“…The elbow joint is surrounded by rich collateral arterial blood supply: the radial artery connects to the proximal part of the brachial artery through the anterior branch of the deep brachial artery, and the ulnar artery has its connection through superior and inferior collateral ulnar arteries (11). Because of this feature, in up to 10% of cases, pulsations of ulnar and radial arteries are present despite blood flow disruption in the brachial artery (3,5,7). In such cases, the physician should be alerted to excessive swelling at the joint and the presence of median nerve palsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients should be assessed for neurovascular injury on arrival to the ED as well as assessment of the wrist and shoulder to out rule a synchronous injury which can occur in 10–15% of cases 1. Brachial artery injury is rare but may occur before or after reduction and thus patients should be closely monitored following reduction 7 8. Stiffness and reduced range of motion can develop following elbow dislocation 2.…”
Section: Discussionmentioning
confidence: 99%
“…19 Most of these injuries are caused by supracondylar fractures, but acute ischemia caused by compression of an abnormally positioned brachial artery by the lacertus fibrosis 20 and thrombosis from elbow dislocation have been reported. 21 Although the overall incidence of brachial artery injury in patients with supracondylar fracture is low, one large series of more than 1000 patients treated in a single institution found a 4% incidence of a pale, pulseless hand at presentation. 22 All of these patients had a Gartland type III fracture pattern.…”
Section: Other Causes Of Closed Arterial Damagementioning
confidence: 99%